Pelatihan Akuntansi Dasar untuk Penyusunan Laporan Keuangan BUMDES di Kecamatan Sungai Kakap - Khristina Yunita; Sari Rusmita; Ira Grania Mustika; Nina Febriana Dosinta; Handi Brata (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2024)
There is quite a lot of potential in the Sungai Kakap sub-district, so it can be developed and managed through Badan Usaha Milik Desa (BUMDes). The results of previous Community Services activities provided input to the Community Services team to provide counseling and guidance regarding the accountability of BumDes in Sungai Kakap District. Accountability as BUMDes responsibility is related to the village administration and governance system, to create transparency. The aim of implementing PKM activities for the accounting study program is to help BumDes managers understand BumDes governance. Then be able to carry out simple accounting practices, help to design product marketing concepts, and strengthen the BUMDES organization. Community Services activities are scheduled in three stages. First, planning by identifying problems that arise in BUMDes management and designing actions to get solutions. Second, preparation with internal coordination of the PKM team, adjusting schedules and locations, as well as preparing materials for mentoring activities. Third, implementation by following up on activity plans and identifying possible problems in implementing Community Services. Basic accounting training for preparing BUMDes financial reports in Kakap District has implications for the preparation of BUMDES financial reports by accounting understanding and accounting standards.